Correlation of Waist to Height Ratio with Leptin Serum Level in Coronary Artery Disease - Damay, Vito; Undarsa, Alberta Claudia (The Indonesian Heart Association, 2017)
Background: Adiposity assessment plays an important role in coronary artery disease (CAD) prevention. One of the adiposity parameter in major CAD management guideline is waist to height ratio (WHtR). Adiposity promotes the pathogenesis of coronary atherosclerosis by involving adipokines released by adipose tissue. Leptin is obesity identic adipokine which is used as prognostic predictor of cardiovascular event. This study aims to analyze correlation between WHtR and leptin serum level. Method: A cross sectional study was performed to 37 stable CAD patients undergone elective coronary angiography in Heart Catheterization Laboratory Dr Hasan Sadikin Hospital, Bandung, West java in July 2014 Results: Mean age of the subjects was 56.7± 9.12 years old with mean age of men (n=32) and women (n=5) were 55.9±9.47 years old and 62±3.54 years old consecutively. There were 30 (81%) subjects classified as obese (WHtR≥0.5) with mean WHtR 0.54±0,06. Median value of leptin serum was 8599.90 pg/ml (780-36929.3 pg/ml). Based on rank-spearman correlation test, a positive moderate correlation was significantly found between WHtR and Leptin serum level (Spearman’s rho = 0.5, p= 0.001). Conclusion: Positive correlation was found between WHtR and leptin serum level. Hence, WHtR might be useful as indicator of leptin serum level which has been used as a prognostic biomarker in CAD patients   Abstrak Latar belakang: Penilaian adipositas merupakan bagian dari upaya preventif penyakit jantung koroner (PJK). Salah satu parameter antropometri adipositas yang digunakan pada panduan tatalaksana PJK adalah pengukuran rasio lingkar pinggang/tinggi badan (LP/TB). Adipositas diketahui berperan dalam patomekanisme terbentuknya aterosklerosis koroner melalui pelepasan adipositokin oleh jaringan adiposa. Leptin merupakan adipositokin identik adiposit yang digunakan sebagai biomarka indikator prognostik kejadian kardiovaskular. Penelitian ini bertujuan untuk menganalisa korelasi LP/TB dengan kadar leptin serum. Metode: Studi potong lintang dengan menganalisis antropometri LP/TB dan kadar leptin serum pada 37 pasien PJK yang menjalani angiografi elektif di Laboratorium Kateterisasi Jantung RSUP Dr.Hasan Sadikin, Bandung, Jawa Barat pada bulan Juli 2014. Hasil: Rerata usia subjek adalah 56.7± 9.12 tahun dengan rerata usia pria (n=32) dan wanita (n=5) secara berurutan adalah 55.9±9.47 tahun dan 62±3.54 tahun. Terdapat 30 (81%) subjek tergolong obesitas (nilai LP/TB ≥0,5) dengan rata-rata LP/TB 0.54±0,06. Nilai median leptin serum 8599.90 pg/ml (780-36929.3 pg/ml). Berdasarkan uji korelasi rank-spearman, terdapat korelasi positif bermakna antara LP/TB dengan kadar leptin serum (Spearman rho = 0.5, p= 0.001). Kesimpulan: Terdapat korelasi positif bermakna antara pemeriksaan antropometri LP/TB dengan kadar leptin serum. Rasio lingkar pinggang/tinggi badan dapat digunakan sebagai salah satu indikator kadar leptin serum yang merupakan biomarka prognostik kardiovaskular.